Competitor Accounting (CA) of Joint Venture Banks - Pokharel, Prakash (KMC Research Journal, 2019)
In order to facilitate the collection and analysis of accounting information related with the competitor in the context of strategic management accounting, the term competitor accounting has been developed. However, no empirical results are available as to the extent to which such information influences strategic decision behavior. Main purpose of this study is to explore the effect of competitor accounting on performance of the joint venture banks, and compare the effectiveness of competitor accounting between those banks. For this structured questionnaire survey with 133 staffs of the concerned banks as well as unstructured interview with 4 senior managers were conducted. Various published and unpublished reports like annual reports of the concerned banks were also used. From the study it is found out that levels of CA formalised application appear limited, especially when compared with a widely held managerial perception that significant benefits could derive from CA. The CA practices noted were conducted in an unstructured and ad hoc manner. CA does not have any effect on performance of Nepalese joint venture banks because of not applying any formalised CA application.The study had /some of the limitations generally associated with a qualitative as well as quantitative study. These limitations include the degree of subjectivity that is invoked when researchers interpret qualitative data, scarcity of various resources, and accuracy of secondary data.The study clarifies the notion of CA and provides an outline of CA management issues arising in the context of a joint venture banks. An outline is provided of those parts of a bank operation that are most likely to be more active in CA, together with empirically informed suggestions with respect to CA uses in a joint venture banks.